Development of Sparkol Videoscribe-Based Learning Media in Enhancing Arabic Vocabulary Mastery for Eighth Grade Students - Adelia Assyifa; Asti Fauziah; Namirotul Qubaiyah (WISE Pendidikan Indonesia, 2023)
Arabic vocabulary mastery remains a significant challenge in language learning, particularly for eighth-grade students in Indonesia. This study addresses the critical issue of enhancing vocabulary retention through innovative learning media. The research aims to develop and evaluate Sparkol Videoscribe-based learning media designed to improve Arabic vocabulary mastery. Utilizing the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), this study was conducted at Daarul Ilmi Integrated Islamic Junior High School in Bandar Lampung in November 2022. The developed media underwent validation by subject matter experts, media experts, and educators, yielding validation scores of 76%, 78%, and 88%, respectively, indicating strong suitability. Attractiveness tests conducted on small and large groups of students resulted in scores of 86% and 89%, categorizing the media as highly engaging. These findings suggest that Sparkol Videoscribe-based media significantly enhances both the effectiveness and engagement of Arabic vocabulary instruction, providing a scalable and impactful solution for Arabic language education in junior high schools.